Visible light-driven methanol dehydrogenation and conversion into 1, 1-dimethoxymethane over a non-noble metal photocatalyst under acidic conditions. Issue 13 (18th June 2018) - Chao, Yuguang; Lai, Jianping; Yang, Yong; Zhou, Peng; Zhang, Yelong; Mu, Zijie; Li, Shiying; Zheng, Jianfeng; Zhu, Zhenping; Tan, Yisheng
Abstract : The dehydrogenation and conversion of methanol into 1, 1-dimethoxymethane (DMM) was achieved over noble metal free photocatalyst CdS/Ni2 P under visible light. Abstract : The dehydrogenation and conversion of methanol into 1, 1-dimethoxymethane (DMM) was achieved over noble metal-free photocatalyst CdS/Ni2 P under visible light. This photocatalytic process for methanol-to-H2 and DMM conversion is efficient and atom economic, with an optimal rate and selectivity of DMM of 188.42 mmol g −1 h −1 and 82.93%, respectively. This work supplies a new green approach for the direct efficient conversion of methanol into DMM and provides a promising avenue for sustainable bio-methanol applications.